The Palgrave Macmillan Dictionary of Women's Biography
XX, 668 p.
Keywords: The Palgrave Macmillan Dictionary of Women's Biography contains details of the lives of over 2100 women from all periods, cultures and walks of life - from queens to TV chefs, engineers to stand up comics, pilots to poisoners. With subsections for further reading, comprehensive subject index and a bibliographical survey, this dictionary of women's biography is an invaluable reference source.